Fracture behaviour of steel fibre reinforced recycled aggregate concrete after exposure to elevated temperatures. (15th December 2016) - Chen, G.M.; Yang, H.; Lin, C.J.; Chen, J.F.; He, Y.H.; Zhang, H.Z.
Highlights: Recycled aggregate concrete (RAC) tested after exposure to high temperatures. Fracture behaviour assessed using the double-K fracture model. High temperature has detrimental effect on fracture properties. Steel fibres increase fracture energy of RAC after high temperature exposure. Steel fibres enhance fracture toughness of RAC after high temperature exposure. Abstract: In the past decade, research on applications of recycled aggregate concrete (RAC), which uses recycled concrete aggregate (RCA), has attracted world-wide interest due to their social, environmental and potential economic benefits. One of the main concerns for using such concrete in buildings is its spalling in fire and post-fire residual mechanical properties. This concern may be alleviated by adding steel fibres to form steel fibre reinforced recycled aggregate concrete (SFRAC). In this study, 60 notched beams were tested to evaluate the fracture behaviour of SFRAC after exposure to elevated temperatures, including the modulus of elasticity (E), fracture energy ( GF ), initiation fracture toughness K Ic ini and unstable fracture toughness K Ic un . The effects of steel fibre volume content (0%, 0.5%, 1% and 1.5%) and exposure temperature (room temperature, 200 °C, 400 °C and 600 °C), were investigated. The test results show that the addition of steel fibres postpones the initiation of cracks and limits their opening in RAC, and thus significantly enhances the fracture energy and fracture toughness of RAC after exposure to high temperatures.